HUBUNGAN ANTARA SIKAPINOVATIF DAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU DI SD NEGERI SE-KECAMATAN KETAHUN - Jasmani Jasmani Jasmani (UNIVERSITAS BENGKULU, 2016)
The purpose of this study is to analyze: 1) the correlation between the innovative attitude of the principal to the teacher performance; 2) the correlation between the principalleadership to the teacher performance; and 3) the correlation of the innovative attitude and the principal leadership with the teacher performance. The method of this study was descriptivecorrelation. The samples were the teachers of Public elementary school in Ketahun district. It was sixty teachers. the results of the study showed that there was a significant correlation between: 1) the innovative attitude of the principal to the teacher performance; 2) the principal leadership to the teacher performance; 3) the innovative attitude and the principal leadership with the teacher performance in Public elementary school in Ketahun District.Keywords: innovative attitude, principal leadership, teacher performance